2016
DOI: 10.1002/cncr.29934
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effects of TERT promoter mutations are enhanced by coexistence with BRAF or RAS mutations and strengthen the risk prediction by the ATA or TNM staging system in differentiated thyroid cancer patients

Abstract: BACKGROUND: Recent reports suggest that mutations in the promoter of the gene encoding telomerase reverse transcriptase (TERT) affect thyroid cancer outcomes. METHODS: In all, 551 patients with differentiated thyroid cancer (DTC) enrolled in this study. The median follow-up duration was 4.8 years (interquartile range, 3.4-10.6 years). RESULTS: TERT promoter mutations were detected in 25 DTCs (4.5%): 2.8% in neither BRAF-mutated nor RAS-mutated tumors, 4.8% in BRAF-mutated tumors, and 11.3% in RAS-mutated tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
4
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(172 citation statements)
references
References 26 publications
9
156
4
3
Order By: Relevance
“…Some groups report that co-occurrence of TERT promoter and BRAF mutations are associated with worse prognosis factors in thyroid cancer (Allory et al 2014, 2016a, Song et al 2016, whereas other authors have not found this association in other series (Melo et al 2014, George et al 2015, Nasirden et al 2016.…”
Section: Tert Promoter Mutations In Thyroid Cancermentioning
confidence: 94%
“…Some groups report that co-occurrence of TERT promoter and BRAF mutations are associated with worse prognosis factors in thyroid cancer (Allory et al 2014, 2016a, Song et al 2016, whereas other authors have not found this association in other series (Melo et al 2014, George et al 2015, Nasirden et al 2016.…”
Section: Tert Promoter Mutations In Thyroid Cancermentioning
confidence: 94%
“…Gland Surg 2016;5(5):495-505 gs.amegroups.com aggressive clinical course. It is believed that more accurate tumor prognostication is possible due to a genetic analysis (55)(56)(57)(58).…”
Section: Ata Modified Initial Risk Stratification Systemmentioning
confidence: 99%
“…This body of evidence led a wide part of literature dealing with DTC to categorise prognostic effect of TERT promoter mutations as dramatic, even overcoming prognostic performance of the BRAF V600E oncogene, which was historically considered as the best molecular prognosticator (as discussed previously). Nevertheless, this was misleading as recently demonstrated by a series of studies performing simultaneous analysis of TERT promoter and BRAF (Xing et al 2014a,b, Liu et al 2014b, Song et al 2016. Indeed, all these papers consistently showed that prognostic effect related to alterations of TERT promoter disappeared or strikingly decreased when mutations occurred separately (Fig.…”
Section: Emerging Molecular Prognosticators: Tert Promoter and Tp53 Mmentioning
confidence: 91%
“…They found that the 2 molecular abnormalities were synergic in increasing the risk of persistent disease, but failed to demonstrate similar interaction for the risk of tumour recurrence. More recently, the aforementioned study by Song (Song et al 2016) showed a synergistic effect between RAS and TERT promoter mutations in worsening clinico-pathological features and outcome of DTC patients, including both tumour recurrence and diseaserelated mortality. Although further studies are needed to assess the actual interplay with RAS status, the presence of TERT promoter mutations may allow the identification of a subgroup of aggressive tumours within both BRAFand RAS-mutated DTC, which represent the main clinicomolecular types (Agrawal et al 2014).…”
Section: Co-occurrence Of Driver Mutationsmentioning
confidence: 99%
See 1 more Smart Citation